Economics of Fiscal Dominance and Ramifications for the Discharge of Effective Monetary Policy Transmission - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields, 2024)
This paper explores the intricate dynamics of fiscal dominance and its profound implications for monetary policy efficacy, contributing to the discourse on the interplay between fiscal and monetary policies. The theoretical foundation critically examines existing literature, integrating empirical evidence to construct a comprehensive understanding. Model blocks strategically elucidate the significance of fiscal variables in shaping monetary transmission mechanisms. The ensuing analysis scrutinises the disruptive potential of fiscal dominance on conventional monetary policy tools. The conclusion navigates policy recommendations, emphasising the necessity of coordinated fiscal-monetary strategies to effectively mitigate inflationary pressures. This research provides a nuanced perspective for policymakers, offering theoretical depth and empirical insights to guide decisions in addressing the complex challenges posed by fiscal dominance in economic governance.